Soil and Water Conservation Practices for Sustained Crop Production on Agricultural Lands of Yamuna Ravines. - Nitant, H.C.; Tiwari, A.K. (Journal of Soil and Water Conservation, 2022)
Ravines constitute nearly 4.0 million ha of land in India of which about a39 million ha is affected along the river Yamuna in Uttar Pradesh. Shallow and medium deep ravines are reclaimed by leveling into terraced fields and used under agricultural land use Poor fertility status and low water holding capacity of soils was reported. Proper agro-techniques in ravine land are necessary in order to achieve higher yield and productivity in addition to suitable soil and water conservation measures. Water harvesting/moisture conservation practices such as land modification, surface mulching and cover crops were found effective in erosion control and in improving the production of crops. Mechanical measures like land leveling and contour bunding have great promise in erosion control and moisture conservation Inclusion of pulses and oilseed crops in soil and water conservation programme has a definite advantage. Use of harvested runoff water for pre sowing irrigation and irrigation at branching and flowering stage in mustard gave better returns. Missing links in research have been identified and future lines of work have been suggested